2016
DOI: 10.1136/bmjopen-2015-010847
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing victimisation to healthcare professionals in Sweden: a constructivist grounded theory study of experiences among men exposed to interpersonal violence

Abstract: ObjectiveTo develop a theoretical model concerning male victims' processes of disclosing experiences of victimisation to healthcare professionals in Sweden.DesignQualitative interview study.SettingInformants were recruited from the general population and a primary healthcare centre in Sweden.ParticipantsInformants were recruited by means of theoretical sampling among respondents in a previous quantitative study. Eligible for this study were men reporting sexual, physical and/or emotional violence victimisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(59 citation statements)
references
References 51 publications
2
57
0
Order By: Relevance
“…The impact of IPVAW on the health (Örmon, Torstensson Levander, Sunnqvist, & Bahtsevani, ; Scheffer Lindgren & Renck, ), economy (Eriksson & Ulmestig, ; Ulmestig & Eriksson, ), and working life (Alsaker et al, ) of victims has been analyzed. Experiences and narratives of male IPV perpetrators (Boethius, ; Edin & Nilsson, ; Gottzén, ; Gottzén, ; Gottzén, , , ; Håland, Lundgren, Lidén, & Eri, ; Hydén, , , 1995; Jansson, ; Lennéer‐Axelson, [1989]; Lundgren, ) and victims (Hellgren, Andersson, & Burcar Alm, ; Nybergh, Enander, & Krantz, ; Simmons, Brüggemann, & Swahnberg, ) have also been studied, as has the importance of social networks for responses to IPVAW (Hydén, ; Hydén, ; Sandberg, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of IPVAW on the health (Örmon, Torstensson Levander, Sunnqvist, & Bahtsevani, ; Scheffer Lindgren & Renck, ), economy (Eriksson & Ulmestig, ; Ulmestig & Eriksson, ), and working life (Alsaker et al, ) of victims has been analyzed. Experiences and narratives of male IPV perpetrators (Boethius, ; Edin & Nilsson, ; Gottzén, ; Gottzén, ; Gottzén, , , ; Håland, Lundgren, Lidén, & Eri, ; Hydén, , , 1995; Jansson, ; Lennéer‐Axelson, [1989]; Lundgren, ) and victims (Hellgren, Andersson, & Burcar Alm, ; Nybergh, Enander, & Krantz, ; Simmons, Brüggemann, & Swahnberg, ) have also been studied, as has the importance of social networks for responses to IPVAW (Hydén, ; Hydén, ; Sandberg, ).…”
Section: Methodsmentioning
confidence: 99%
“…Abused men have had trouble defining themselves (Hellgren et al, 2015;Jarnkvist & Brännström, 2016b;Simmons et al, 2016), and being supported as victims (e.g., BRÅ, 2010;Kullberg et al, 2015;Simmons et al, 2016;Hellgren et al, 2015), as exposure to violence from female partners is not included in normative understandings of masculinity, according to which men are expected to be stronger and exert more power in heterosexual relationships (Jarnkvist, 2015). Conforming to hegemonic masculinity has been identified as an influence towards IPV nondisclosure in health care, while help is often sought from female professionals (Simmons et al, 2016). Victimized men have further described being scorned with sexist or homophobic language, by violent partners, for not fulfilling masculinity norms (Nybergh et al, 2015).…”
Section: Layers Of Dominancementioning
confidence: 99%
“…Previous qualitative studies reported that men's concerns about not appearing "weak" are a factor that influences men's help-seeking intentions after experiences of interpersonal violence [51,52]. Therefore, it may be important for physicians to carefully avoid communicating to their patients opinions that would imply that male victims of interpersonal violence are weak in order to not discourage some male victims of interpersonal violence from asking for help [13,53]. One pattern of gender role conflict was positively associated with men's wish to be asked in patient-physician conversations about potential interpersonal violence.…”
Section: Masculinity and Conversations About Interpersonal Violencementioning
confidence: 99%
“…Qualitative studies support the hypothesis that gender role conflict may be negatively associated with men's wish for patient-physician conversations to include questions about interpersonal violence. In qualitative studies men who were attempting to adhere to masculine gender role ideologies reported that it was not likely that they would divulge their experience of interpersonal violence to a healthcare professional [13]. Especially men's tendency to restrict emotional expressivity and their reluctance to talk about emotional and intimate issues seemed to influence men's willingness to talk or their wish to be asked about violence they might have experienced [29].…”
mentioning
confidence: 99%
“…[4][5][6] The available literature shows that IPV elements in medical curricula are not standardized and that medical doctors hardly receive effective or any training at all resulting in a lack of appropriate competencies to deal with IPV. 7,8 In contrast, other research findings show that IPV curricula can help in improving medical doctors' self-efficacy to identify and manage victims of IPV leading to an increase in referral rates. [9][10][11] Although IPV is increasingly recognized as a public health issue that can lead to fatal outcomes, few studies address how medical doctors in Africa are prepared to deal with victims.…”
Section: Introductionmentioning
confidence: 99%